Academic Reflection – Gender, Subjectivity and Criminal Responsibility - Loughnan, Arlie (feminists@law, 2018)
The topic of gender and criminal responsibility has long attracted critical scholarly attention. Several cohorts of feminist scholars in law, criminology and history have examined various dimensions of women’s responsibility for crime. Nicola Lacey’s work is at the forefront of this critical examination of gender and criminal responsibility. Lacey tackles this topic from both a feminist legal theory perspective and a criminal law theory perspective. This short paper offers some further comments on gender and criminal responsibility, with an examination of what I call the atypical criminal legal forms that govern women’s responsibility for crime in the current era. In so doing, I consider how some of the different dimensions of Lacey’s impressive oeuvre come together.